Evaluación del liderazgo educativo en el ITS Dr. José Ochoa león de pasaje y su relación con el contexto actual. - Narváez Ramón, César Ramiro (2017)
This research aims to determine the level of impact of the current educational leadership in the Instituto Tecnológico Superior José Ochoa León of the city of Pasaje, noting that nowadays from the transmodern perspective the leadership must be shared horizontally, these processes have allowed in many companies of the world the business success, which is achieved through the sum of skills, Capacities, competencies, abilities, techniques, also highlights the characteristics of the current model of educational leadership and the alternative proposal that is implemented in the Instituto Tecnológico Superior José Ochoa León of the city of Pasaje, and the results related to the institutional development that are obtained with the current model of educational leadership that are executed in the Instituto Tecnológico Superior José Ochoa León of the city of Pasaje, the methodology of the present work is the field research and the analysis of quantitative and qualitative variables, this project is based on the academic and administrative development regarding leadership in the current context.